A 3D ordered hierarchically porous non-carbon electrode for highly effective and efficient capacitive deionization. Issue 26 (24th June 2019) - Wu, Yuchen; Jiang, Gaopeng; Liu, Guihua; Lui, Gregory; Cano, Zachary Paul; Li, Qian; Zhang, Zhen; Yu, Aiping; Zhang, Zisheng; Chen, Zhongwei
Abstract : A nanoengineered 3D hierarchical ordered porous titanium nitride electrode is applied as an effective and efficient non-carbon electrode to deliver outstanding salt adsorption capacity and record-breaking salt adsorption rate in a capacitive deionization cell. Abstract : In this work, three-dimensional ordered mesoporous titanium nitride (3DOM-TiN) has been synthesized via a templating method as a novel high-performance non-carbon capacitive deionization (CDI) electrode material. The dual ion electrosorption mechanisms, fast ion diffusion and rapid charge transfer enabled by the multiple advantageous features of the 3DOM-TiN electrode facilitate an outstanding CDI salt adsorption capacity (SAC) as high as 23.6 mg g −1 and a record-breaking maximum salt adsorption rate (SAR) of 3.2 mg g −1 min −1 in 500 mg L −1 NaCl solution at an applied voltage of 1.2 V. Such excellent CDI performance in addition to excellent cycling stability not only ranks the 3DOM-TiN electrode as one of the most promising electrodes for future CDI applications but also confirms the great potential of nanoengineered non-carbon electrodes for next-generation CDI cells.